Adaptive adjustment of offspring sex ratio and maternal reproductive effort in an iteroparous mammal - Holand, Øystein (The Royal Society, 2005)
Large mammals in seasonal environments have a pattern of high-reproductive synchrony in spring, but how the timing of reproduction affects resource allocation decisions at different stages of the reproductive cycle remains largely unexplored. By manipulating the timing of conception in reindeer (Rangifer tarandus), we tested how the timing of conception affected sex ratio, gestation length and weight development of mother and offspring. Females that conceived at their first ovulation within the rut had a 60.5% probability of producing a male; in contrast, females that conceived a cycle later had a 31.3% probability of producing a male. Late conceiving females had gestation times that were 10 days shorter and the calves were 0.6 kg (9.2%) lighter at birth and 7.4 kg (14.7%) lighter in autumn. Over the year, female weight changes was similar between the groups suggesting reindeer follow a bet-hedging strategy; reducing the quality of this year's offspring to ensure their own future reproduction and survival. Harvesting is often selective leading to skewed sex ratios and age structure, which may influence the timing of reproduction due to females hesitation to mate with young males. Whenever this hesitation is strong enough to increase the frequency of recycling, harvesting is likely to have profound life history consequences.